Atrial fibrillation in Brugada syndrome: Current perspectives. (29th January 2020) - Vlachos, Konstantinos; Mascia, Giuseppe; Martin, Claire A.; Bazoukis, George; Frontera, Antonio; Cheniti, Ghassen; Letsas, Konstantinos P.; Efremidis, Micheal; Georgopoulos, Stamatis; Gkalapis, Charis; Duchateau, Josselin; Parmbrun, Thomas; et al.
Abstract: The incidence of atrial fibrillation (AF) in Brugada syndrome (BrS) has been reported at between 9% and 53% by different series, but the true prevalence is unknown. However, AF may be the presenting feature in some patients. The underlying mechanisms for AF may be a combination of multiple factors, genetic or acquired, that may impact upon autonomic function, atrial structure, and conduction velocities or other unknown factors. The presence of AF has been associated with a more malignant course, with a greater incidence of syncope and ventricular arrhythmias, thus acting as marker of more advanced disease. Regarding the management of patients with AF, antiarrhythmic drugs effective in preventing malignant arrhythmias in BrS such as quinidine or invasive treatment with pulmonary vein isolation (PVI) may be useful in AF treatment. In this review, we aim to present the current perspectives regarding the genetics, pathophysiology, management, and prognosis of AF in patients with BrS.